성범죄 재범자의 경험에 관한 사례연구: 성범죄 3회 이상인 사람을 대상으로 - 윤지인(홍익대학교 교육학과 박사수료; 이홍숙 (교정연구, 31(3), 2021)
본 연구의 목적은 성범죄를 재범한 자들이 재범에 이르게 된 원인과 이를 고착시킨성장 과정을 알아보고 재범과정 및 이 과정에서 겪는 정서와 사고의 변화 등, 성범죄재범자들의 경험을 심층적으로 이해하고자 하는 것이다. 이를 위하여 성범죄로 유죄선고를 3회 이상 받은 총 5명의 성범죄 재범자들을 대상으로 심층 면담하였고, 질적사례연구의 방법을 사용하여 주제분석을 실시하였다. 분석결과 성범죄 재범자들은 성장과정에서 열악한 가정환경과 일탈적 환경으로 부적응과 일탈을 겪고, 이런 과정에서 강한 애정욕구를 가졌던 반면, 친밀한 관계능력의 부족으로 이성관계의 어려움을겪으며 살아왔다. 또한, 어린 시절 성폭력 피해나 가해를 직･간접적으로 겪으며 성적각성과 함께 내적 갈등 속에서 성범죄에 대한 인식 없이, 호기심과 성적 자극 속에가해자가 되는 것을 볼 수 있었다. 즉 성적 트라우마를 겪은 피해자에서 성폭력 가해자가 되었다. 친밀감 부재와 감각적인 성적 만남의 결과는 이성관계에 대해 쉽게 싫증을 내게 하며, 더욱 감각적 성관계에 심취하게 하였다. 강한 성적 욕구로 충동조절에 어려움을 겪으며, 일반적이지 않은 성적 일탈과 환상을 가지는 등 성중독의 특성을 보였다. 어린 나이에 겪은 비정상적인 성 경험, 문란하고 강압적이고 감각적인 성욕구해소는 성통념과 성인지 왜곡을 강화시켜 성폭력에 대한 범죄 인식을 결여시키는 것으로 나타났다. 폭력과 무관심 등 애정결핍과 가혹한 가정환경, 비정상적이고 일탈적이고 감각적인 성 경험은 애정결핍을 강화시켜 성에 더욱 고착되게 하는 것으로 보인다. 이러한 연구결과를 토대로 이들에게 깊이 내재해 있는 관심과 애정에 대한 욕구를해소하는 것이 중요하며, 집단 치료프로그램과 함께 성범죄 재범자에게 맞는 개인 심리치료와 성폭력 피해와 가해 경험에 대한 외상을 집중적으로 다루는 치료적 접근, 그리고 성중독에 대한 치료의 필요성을 제언하였다. In this study, we tried to understand the characteristics of sex offenders by interviewing their experiences in a grown-up process and the cause of their re-sexual crimes related to the change of their emotion and attitude during conducting sexual violence, and tried to utilize the data for developing a recurrence-prevention program for sexual criminals studying the cases of the sexually re-criminal violence, Using the qualitative case study method, five re-criminals of sexual crimes were interviewed to collect data and to study subject analysis. According to the result of analysis, they have been suffered the lack of intimacy, maladjustment and deviation due to a poor social environment such as poverty, indifference and so on, during a grown-up process. And they have been lived without any attention from their family or others, and hard to get good relationship with any others even though eager to have strong intimacy for love. When they were young, they experienced sexual awakening and conflict caused by sexual damages, and became a perpetrator in curiosity without any criminal awareness. In other words they became a sex offender from a victim of sexual trauma. He showed characteristics of sexual addiction, such as boredom caused by lack of intimacy and sensory sexual relations, difficulties in strong sexual desire and impulsion control, and having unusual sexual deviations and fantasies. Distorted adult consciousness weakened the perception of crime and showed a weak perception and attitude toward crime with a light attitude. The harsh family environment, such as violence and indifference, and abnormal and sensuous sex experiences seem to strengthen the lack of affection, fix to sex. Based on these findings, it is importance of resolving the desire for deep interest and affection in them, along with a collective treatment program, to focus on personal psychotherapy for repeat sex offenders, trauma to sexual violence, and sexual abuse. KCI Citation Count: 0